Communicating corporate change : a practical guide to communication and corporate strategy - Quirke, Bill, 1954-; Quirke, Bill, 1954- (London ; New York : McGraw-Hill, 1996)
Getting communication right is vital to making change happen inside organizations - yet poor internal communication is routinely sabotaging efforts for change. The great majority of employees do not know where their companies are going or what they are trying to achieve, but are convinced they themselves are already doing a good job. They get 70 per cent of their information on the grapevine, believe management has a hidden agenda, and feel saying what they really think would be a career limiting move. Communicating Corporate Change tackles these problems with a framework for identifying the right internal communication strategy. It focuses on linking the communication strategy directly to the business strategy, and gives insights into how to make a new strategy work or identify where a current strategy is failing.
Now updated and expanded to cover the impact of new technology, the role of the internal communicator, and the future of internal communication, it takes a practical look at the Catch 22s that dog communication, using real examples from a variety of key businesses.
1. Communicating in a world of change -- 2. The business of communication -- 3. Structure, identity and values -- 4. Communicating for change -- 5. Customer and quality communication -- 6. Using internal research to create change -- 7. Communicating in teams -- 8. Orchestrating communication.
"A new, revised paperback of the ... Communicating change."
Includes bibliographical references (p. 316-318) and index.
Keywords: Communication in management; Organizational change; Organizational innovation